Adaptation of Popular Culture in Digital Fatwa on Social Media - Dony Arung Triantoro; Fathayatul Husna; Rizky Amalia Syahrani; Futri Syam; Ainal Fitri (Islam Realitas: Journal of Islamic and Social Studies, 2023)
The development of modern information technology and mass education does not necessarily weaken traditional religious authorities such as Habib. One of Habib's efforts to survive amidst the development of contemporary information technology is to deliver fatwas with popular culture. Fatwa is the main channel for Habib to establish and strengthen his authority. This article examines the adaptation of popular culture in digital fatwas on social media. This study uses a qualitative method. The data collection technique was carried out through netnography. Then, the data was analyzed using thematic analysis. The results of this research show that there are several forms of adaptation of popular culture carried out by Habib Husein Ja'far in conveying his fatwa on social media. First, Habib Husein Ja'far adapted slang language in conveying his fatwa on social media. Second, Habib Husein Ja'far adopted Japanese culture. Third, Habib Husein Ja'far visualized his fatwa in modern comics. Based on these findings, this study concludes that the development of modern technology has provided opportunities for habib to deliver their fatwas digitally. The form of the fatwa delivered by Habib adopts the form of popular culture, thereby attracting the attention of modern young Muslims.Perkembangan teknologi informasi modern dan pendidikan massal tidak lantas melemahkan otoritas keagamaan tradisional seperti habib. Salah satu upaya yang dilakukan habib untuk bertahan di tengah perkembangan teknologi informasi modern adalah dengan mengemas fatwa melalui budaya populer. Fatwa menjadi saluran utama bagi seorang habib untuk membentuk dan menguatkan otoritasnya. Artikel ini bertujuan untuk mengkaji adaptasi budaya populer dalam fatwa digital di media sosial. Penelitian ini menggunakan metode kualitatif. Adapun teknik pengumpulan data dilakukan melalui netnografi. Kemudian data dianalisis menggunakan analisis tematik. Hasil penelitian ini menunjukkan bahwa ada beberapa bentuk adaptasi budaya populer yang dilakukan Habib Husein Ja’far dalam menyampaikan fatwanya di media sosial yaitu: Pertama, Habib Husein Ja’far mengadaptasi bahasa slang dalam menyampaikan fatwanya di media sosial. Kedua, Habib Husein Ja’far mengadaptasi budaya Jepang. Ketiga, Habib Husein Ja’far memvisualisasikan fatwanya ke dalam komik modern. Berdasarkan temuan tersebut, penelitian ini menyimpulkan bahwa perkembangan teknologi modern telah memberikan peluang kepada habib untuk menyampaikan fatwanya secara digital. Bentuk fatwa yang disampaikan oleh habib mengadopsi bentuk budaya populer, sehingga menarik perhatian anak muda Muslim modern.